Impact of allogeneic dental pulp stem cell injection on tissue regeneration in periodontitis: a multicenter randomized clinical trial - Yi Liu; Yitong Liu; Jingchao Hu; Jianhui Han; Lin Song; Xu Liu; Nannan Han; Xia Xia; Jia He; Hongfang Meng; Meng Wan; Haojie Wang; et al. (Signal Transduction and Targeted Therapy)
Abstract Periodontitis causes the destruction of tooth-supporting tissues, and current therapies for periodontal regeneration are invasive. In this study, a human dental pulp stem cell (DPSC; hDP-MSC) injection was developed to promote periodontal regeneration through a non-invasive procedure. A total of 132 patients with chronic periodontitis (158 teeth) from two centers in China were included. Thirty-six were randomly assigned to different DPSC dose groups (ranging from 1 × 106 to 1 × 107 DPSCs per tooth, with nine injected with saline only), and 96 were randomly assigned to a single-injection group (1 × 107/0.6 mL DPSCs), a double-injection group (1 × 107/0.6 mL DPSCs × 2), or a saline group, in a 1:1:1 ratio. At 6 months post-therapy, attachment loss (AL), periodontal probing depth (PD), gingival recession (GR), tooth mobility (TM), and bone defect depth (BDD) were examined. The primary outcome was AL. DPSC injection resulted in greater improvement in BDD (0.30 ± 0.484 mm) compared to saline injection (0.04 ± 0.315 mm). Post hoc analysis showed that DPSC injection had significantly better outcomes in patients with stage III periodontitis (AL ≥ 5 mm): 54 patients received DPSCs, and 40 received saline. AL improved by 1.67 ± 1.508 mm in the DPSC group (26.81% improvement) and by 1.03 ± 1.310 mm in the saline group (17.43% improvement). The therapeutic effects encompassed improvements in both soft and hard tissues. In summary, DPSC injection was safe and improved clinical outcomes compared to saline injection in patients with stage III periodontitis. Larger trials are warranted to validate these findings (ClinicalTrials.gov registration: NCT05924373).